Coronal Magnetometry - Tomczyk, Steven; Zhang, Jie.; Bastian, Timothy; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This volume is a collection of research articles on the subject of the solar corona, and particularly, coronal magnetism. The book was motivated by the Workshop on Coronal Magnetism: Connecting Models to Data and the Corona to the Earth, which was held 21 - 23 May 2012 in Boulder, Colorado, USA. This workshop was attended by approximately 60 researchers. Articles from this meeting are contained in this topical issue, but the topical issue also contains contributions from researchers not present at the workshop. This volume is aimed at researchers and graduate students active in solar physics. Originally published in Solar Physics, Vol. 288, Issue 2, 2013 and Vol. 289, Issue 8, 2014.
Preface -- From Forbidden Coronal Lines to Meaningful Coronal Magnetic Fields -- Magnetic Field Extrapolations into the Corona: Success and Future Improvements -- Three-Dimensional Nonlinear Force-Free Field Reconstruction of Solar Active Region 11158 by Direct Boundary Integral Equation -- Magnetic Field Diagnostics and Spatio-Temporal Variability of the Solar Transition Region -- Magnetography of Solar Flaring Loops with Microwave Imaging Spectropolarimetry -- Measuring the Magnetic-Field Strength of the Quiet Solar Corona Using “EIT Waves” -- Observations of a Quasi-periodic, Fast-Propagating Magnetosonic Wave in Multiple Wavelengths and Its Interaction with Other Magnetic Structures -- Coronal Cavity Survey: Morphological Clues to Eruptive Magnetic Topologies -- Polarimetric Properties of Flux Ropes and Sheared Arcades in Coronal Prominence Cavities -- Observations of Coronal Mass Ejections with the Coronal Multichannel Polarimeter -- Near-Limb Zeeman and Hanle Diagnostics -- 3D Coronal Density Reconstruction and Retrieving the Magnetic Field Structure during Solar Minimum.
Keywords: Space sciences; Atmospheric sciences; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Atmospheric Sciences